Rola normy prawnej w przekładzie przepisów prawnych - Panek, Grzegorz (Investigationes Linguisticae, 2009)
If norms, as understood in the theory of law, are mental representations of legal provisions, the latter viewed as a unit of text, one may reach the conclusion that equivalent translation of a legal provision is a rendition from which identical norms may be mentally inferred. In this paper, we are going to show how norms inferred from the source text provision may profile the expressions used in the target text. The norm-based approach opens up space for cognitive analysis, since it is the competent interpreter’s mental semantic matrix that determines the norm, understood as an output of interpretation.